Impact of bio-palladium nanoparticles (bio-Pd NPs) on the activity and structure of a marine microbial community. (January 2017) - Nuzzo, Andrea; Hosseinkhani, Baharak; Boon, Nico; Zanaroli, Giulio; Fava, Fabio
Abstract: Biogenic palladium nanoparticles (bio-Pd NPs) represent a promising catalyst for organohalide remediation in water and sediments. However, the available information regarding their possible impact in case of release into the environment, particularly on the environmental microbiota, is limited. In this study the toxicity of bio-Pd NPs on the model marine bacterium V. fischeri was assessed. The impacts of different concentrations of bio-Pd NPs on the respiratory metabolisms (i.e. organohalide respiration, sulfate reduction and methanogenesis) and the structure of a PCB-dechlorinating microbial community enriched form a marine sediment were also investigated in microcosms mimicking the actual sampling site conditions. Bio-Pd NPs had no toxic effect on V. fischeri . In addition, they had no significant effects on PCB-dehalogenating activity, while showing a partial, dose-dependent inhibitory effect on sulfate reduction as well as on methanogenesis. No toxic effects by bio-Pd NPs could be also observed on the total bacterial community structure, as its biodiversity was increased compared to the not exposed community. In addition, resilience of the microbial community to bio-Pd NPs exposure was observed, being the final community organization (Gini coefficient) of samples exposed to bio-Pd NPs similar to that of the not exposed one. Considering all the factors evaluated, bio-Pd NPs could be deemed as non-toxic to the marine microbiota in the conditions tested. This is the first study in which the impact of bio-Pd NPs is extensively evaluated over a microbial community in relevant environmental conditions, providing important information for the assessment of their environmental safety. Graphical abstract: Highlights: Bio-Pd NPs are deemed not toxic in standard V. fischeri ecotoxicity test. Impact of Bio-Pd NPs tested on microbial community in its native sediment and water. Bio-Pd NPs impact is limited to few respiratory activities. Microbial community is resilient to bio-Pd NPs. Abstract : Bio-Pd NPs are non-toxic towards V. fischeri and have a limited impact on a marine microbial community in site-mimicking microcosms.